PENGARUH SKEPTISISME PROFESIONAL, ETIKA, DAN KOMPETENSI TERHADAP KETEPATAN PEMBERIAN OPINI AUDIT - Ullan Uchi Ramanda, (2021)
This study aims to determine the effect of professional skepticism, ethics and competence on the accuracy of giving an audit opinion. The sample of this study is the auditor at the South Jakarta Public Accounting Firm. The sampling technique used was purposive sampling method. The sample in this study were 88 respondents from 19 South Jakarta Public Accounting Firms. The data used in this study is primary data, namely the provision of a questionnaire to the auditor. Testing the hypothesis of this study using Multiple Linear Regression Analysis using Statistics Program and Service Solution (SPSS) version 25 and a significance level of 5%. The results of the study partially show that the variables of professional skepticism, ethics and competence have a significant effect on the accuracy of giving an audit opinion.